Computers and organisational structure: a sociological perspective. (4th August 2014) - Phillips, Nelson; Anderson, Clarence
The introduction of large–scale, integrated computer systems into corporations, government departments, and other organisations is a relatively new phenomenon, but one which has significant consequences for organisational structure. While existing sociological models provide significant insight into more traditional organisations, they fall short when applied to these new hybrid human/computer organisations. This paper is an attempt to develop a more comprehensive model of the human/computer organisation. The paper begins with a presentation of a typology which identifies organisations which lie outside of the realm of the more traditional sociological models. Next, the work of four important social scientists, Tonnies, Weber, Durkheim, and Freud, is reviewed, assessing the applicability of their work to the human/computer organisation. Finally, a new model is introduced which integrates the main themes of the more traditional models with the hypothesised characteristics of a large–scale, integrated computer system. The ramifications of the model are then discussed and some organisational considerations raised.